Relational Strengths in Interracial/Intercultural Marriage Insights from Four Korean-Caucasian Couples - Yun, Myounghun (2015)
Based on in-depth interviews with four Korean-Caucasian couples, this article explores the relational strengths and resilience of intercultural couples cultivated in the process of forming couple identity, communicating, and practicing marital mutuality. It then delineates some implications for pastoral theology and care emerging from the voices and narratives of the couples. The currently existing literature focuses predominantly on identifying differences, challenges, and struggles in interracial/intercultural marriage (e.g., psychological stressors, relational conflict, and complexities around childrearing). The literature tends to engender and reinforce the misconception that intercultural marriage is fragile or more dysfunctional than intraracial/intracultural marriage. By appropriating the intercultural approach (Lartey, 2003), this article acknowledges that every couple is in some respects: (a) like all other couples; (b) like some other couples; and (c) like no other couple. This article helps to increase the appreciation of cultural difference and the commonality of intercultural couples, along with the unique and universal aspects of these families, and thus helps us move towards a more just and holistic framework for caring for intercultural couples and families.
Keywords: Intercultural/interracial marriage; Korean-Caucasian; Communicative competence; couple identity; Mutuality; relational strengths